Biological characteristics and pathogenicity of Acanthamoeba - Wang, Yuehua; Jiang, Linzhe; Zhao, Yitong; Ju, Xiaohong; Wang, Le; Jin, Liang; Fine, Ryan D.; Li, Mingguang (Frontiers in Microbiology, 2023)
Acanthamoeba is an opportunistic protozoa, which exists widely in nature and is mainly distributed in soil and water. Acanthamoeba usually exists in two forms, trophozoites and cysts. The trophozoite stage is one of growth and reproduction while the cyst stage is characterized by cellular quiescence, commonly resulting in human infection, and the lack of effective monotherapy after initial infection leads to chronic disease. Acanthamoeba can infect several human body tissues such as the skin, cornea, conjunctiva, respiratory tract, and reproductive tract, especially when the tissue barriers are damaged. Furthermore, serious infections can cause Acanthamoeba keratitis, granulomatous amoebic encephalitis, skin, and lung infections. With an increasing number of Acanthamoeba infections in recent years, the pathogenicity of Acanthamoeba is becoming more relevant to mainstream clinical care. This review article will describe the etiological characteristics of Acanthamoeba infection in detail from the aspects of biological characteristic, classification, disease, and pathogenic mechanism in order to provide scientific basis for the diagnosis, treatment, and prevention of Acanthamoeba infection.